Life-cycle-integrated thermoeconomic and enviroeconomic assessments of the small-scale-liquefied natural gas cold utilization systems - Kanbur, Baris Burak (2021)
Small-scale-liquefied natural gas (LNG) cold-utilized power generation systems are the sustainable solutions in the rural and inland areas where the large-scale power generation is infeasible. This study investigates three different small-scale LNG cold-utilized power generation systems, which are called as the single, combined, and carbon dioxide (CO2)–reduced combined systems according to their design details. The assessments are done according to the life-cycle-based enviroeconomic and life-cycle-integrated thermoeconomic assessment (LCiTA) models that are recently developed and new approaches, in order to better monitor their feasibilities in real operations. The life-cycle-based enviroeconomic assessment shows that the combined system has the lowest environmental payback period with 7.35 years that is nearly 6 months and 1 year lower than the single and CO2-reduced combined systems, respectively. The LCiTA study deduces that the combined system has the minimum levelized product cost while the single system has the highest values. The integration of CO2 capture components increases the levelized product cost nearly by 16.0% in the combined design, but the levelized product cost value is still found lower than the single system. Moreover, the sustainability performance of the systems is evaluated according to the improved sustainability index calculated by the life-cycle-integrated fuel and destruction costs. The index value of the combined system is twice that of the single system. The multiobjective optimization study is performed in cases of closed operation rooms. The best trade-off points are found in the close ambient air temperature range between 300.50 and 302.00 K. To observe the dynamic outdoor performance, the finite sum approach is applied for the LCiTA model. The highest fluctuations are seen for the CO2-reduced combined system while the smallest fluctuations belong to the combined system.